2013
DOI: 10.1016/j.foodchem.2012.12.067
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid and calcium co-supplementation improves bone health in ovariectomised mice

Abstract: Osteoporosis is a significant health concern for the elderly; conjugated linoleic acid (CLA) has been shown to improve overall bone mass when calcium is included as a co-supplement. However, potential effects of CLA and calcium on bone mass during a period of bone loss have not been reported. The purpose of this study was to determine how dietary calcium modulates the effects of conjugated linoleic acid (CLA) in preventing bone loss, using an ovariectomised mouse model. CLA supplementation significantly preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Moreover, CLA supplementation reduced the rate of bone resorption in adult OVX rats (21), and has been shown to improve immunity and bone formation (29). Very recently, Park et al demonstrated that CLA improved bone health of ovariectiomized ICR mice supplemented with calcium (37). However, not all have been able to confirm the beneficial effects of dietary CLA supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CLA supplementation reduced the rate of bone resorption in adult OVX rats (21), and has been shown to improve immunity and bone formation (29). Very recently, Park et al demonstrated that CLA improved bone health of ovariectiomized ICR mice supplemented with calcium (37). However, not all have been able to confirm the beneficial effects of dietary CLA supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Given that CLA modulates PGE 2 activity, it is possible that CLA supplementation could reduce bone loss in postmenopausal women through this mechanism. The majority of the previous studies are of short term (4-12 weeks) and do not include data on bone loss in ovariectomized mice fed CLA alone (11, 37). There was a report of beneficial effects from short-term treatment of CLA (9 weeks) against ovariectomy-induced bone resorption in rat (21).…”
Section: Introductionmentioning
confidence: 99%
“…It is still unknown whether the action of CLA on body fat reduction in postmenopausal model is estrogen‐mimetic or not. Animal studies showed that CLA reduced body weight in an estrogen‐deficient OVX model in a similar manner to the sham model, which uses the physiologic range of estrogen (Kanaya and Chen ; Park and others ). These findings suggest that CLA has an antiobesity effect in mice independent of estrogen levels.…”
Section: Cla In the Prevention Of Menopausal Symptomsmentioning
confidence: 91%
“…It is known that estrogen deficiency causes bone loss as a result of accelerated osteoclastic bone resorption with increased prostaglandin E 2 production (Kanematsu and others ). In animal studies using ovariectomy (OVX)‐induced estrogen‐deficient rodent models, CLA has shown to prevent bone loss and improve bone formation (Kelly and Cashman ; Park and others ; Rahman and others ). In particular, CLA supplementation dose dependently reduced prostaglandin E 2 biosynthesis that were increased in OVX control, concomitant with reduction of urinary pyridinoline and deoxypyridinoline (markers of bone resorption) excretion in bone organ culture from OVX rats (Kelly and Cashman ).…”
Section: Cla In the Prevention Of Menopausal Symptomsmentioning
confidence: 99%
See 1 more Smart Citation